President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2019)
My name is Cathleen Ferguson and I am your new ORNAC President. I am also Past President as I served as ORNAC President from 2015-2017. I am stepping back into the President role for another term due to the fact that the President-Elect had to, unfortunately, step down. Taking on a leadership position can be challenging at anytime but stepping into a vacant position and not having the full term as President Elect to transition into this role is a bit daunting. I made the decision to step forward in order to support ORNAC in a leadership capacity, to bring my previous experience to the position, and to help lead the next phase of ORNAC’s development.